Normally solvable operators and differential equations of infinite order - Korobeinik, J. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ю. Ф. Коробейник. Нормально-разрешимые операторы и дифференциальные уравнения бесконечного порядка J. Korobeinikas. Normaliai išsprendžiami operatoriai ir begalinės eilės diferencialinės lygtys